Investigating a Tecnologia Social from the Perspective of ActorNetwork Theory and After - Bignetti, Bernardo; Petrini, Maira (Organizações & Sociedade, 2025)
The aim of this research is to identify and analyze the local socio-technical readjustments and the heterogeneous network involved in bringing a technology for the social closer to a tecnologia social (TS) as a social construct. Technologies as a social foundation, represented by tecnologias sociais, show a way to create, develop and implement technology aimed at solving social problems. In Latin America, especially in Brazil, two visions are used to characterize tecnologia social: (i) TS as a social construct, in which the technology is built and/or readapted through sociotechnical adjustments with the participation of the local community, and (ii) technology for the social, in which the technology is transferred via programs, artifacts, or methodologies that improve the lives of the assisted community. We studied a replication of an entrepreneurial education program for vulnerable young people, which is considered a technology for the social because the program has its own methodology and was not developed with the participation of the community involved. We adopted the theoretical-methodological basis of Actor-Network Theory (ANT), in its version Actor Network Theory and After (ANT and After), based on three elements: enactment, hinterland and political ontology. Our results show how a technology for the social for entrepreneurial education can be brought closer to a TS as a social construct, allowing us to elaborate two points of discussion. These points constitute a contribution both to theory, thinking about future research agendas, and to the practice of technology for the social programs, offering opportunities for socio-technical adaptations that take into account local knowledge, thus promoting social transformation. In addition, another theoretical contribution is to illustrate the use of ANT and After concepts for TS studies, meeting the need to avoid using ANT in a simplistic way, as a mere tool to study an artifact.